Performance of NGA Models in Predicting Ground Motion Parameters of The Strong Earthquake - Lindung Zalbuin Mase (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
Next Generation Attenuation (NGA) West 1 and 2 models are employed to predict the ground motion parameters of strong earthquake during the 6.9 Mw Kobe Earthquake in 1995. This study is initiated by collecting the data of ground motion parameters of the earthquake. Furthermore, the ground motion prediction is performed by using the NGA models. There are three ground motion parameters observed, i.e. peak ground acceleration (PGA), spectral acceleration (SA) at 0.2 second and SA at 1 second. The performances of the models are evaluated by using the Residual Values and Root Mean Square (RMS) Error. The results show that the NGA models could predict the ground motion parameters quite appropriately. It can be seen from the correlation values of the observed and the predicted values, which is relatively consistent each other, especially for peak ground acceleration. In general, this study could recommend the procedure in selecting the attenuation model for strong earthquakes. The study framework could be implemented to predict the ground motion in other regions.